THE MARINE ECOLEXICON OF THE NORTHERN COAST OF OESOKO VILLAGE - Nahak, Kristofel Bere; Mahinet, Jefrianus; Sari, Nila Puspita; Dapubeang, Abdul Rahim Arman Putera (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Ilmu Pendidikan, Universitas Timor, 2025)
This study aims to describe the marine eco-lexicon of the Dawan community in Oesoko Village, Timor Tengah Utara Regency, and analyze its meanings based on Haugen’s three-dimensional ecolinguistic approach: ideological, sociological, and biological. A qualitative descriptive method was employed, with data collected through participatory observation, in-depth interviews, documentation, and audio recording. The results show that the Oesoko community possesses a wide range of lexicons representing maritime activities such as fishing, salt processing, and net mending. These lexicons reflect ecological knowledge, cultural values, and the community’s social structure. The ideological dimension reveals the belief systems embedded in maritime practices; the sociological dimension highlights collective work and intergenerational knowledge transmission; and the biological dimension emphasizes the traditional yet intensive use of natural resources. Thus, the eco-lexicon not only functions as a communication tool but also as a reflection of local cultural and ecological identity that must be preserved.